2016
DOI: 10.2174/1874325001610010900
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite Effect on the Degradation, Osteoconduction and Mechanical Properties of Polymeric Bone Tissue Engineered Scaffolds

Abstract: BACKGROUNDStatistical reports show that every year around the world approximately 15 million bone fractures occur; of which up to 10% fail to heal completely and hence lead to complications of non-union healing. In the past, autografts or allografts were used as the “gold standard” of treating such defects. However, due to various limitations and risks associated with these sources of bone grafts, other avenues have been extensively investigated through which bone tissue engineering; in particular engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…The osteoconductive/osteoinductive, biocompatibility and bioactivity properties of nanoHA materials [7,28] combined with the injectability, biocompatibility and biodegradation properties of Alg polymers [29,30] can improve the physic-chemical and cell adhesion/tissue development of the attained composites, enhancing bone tissue regeneration [31][32][33]. However, these properties could be dependent on the amount of ceramic nanoparticles used within the polymer-based composite, as observed by other authors [21][22][23]. In this context, in the present study, the influence of nanoHA content on an alginate-based hydrogel system was studied, regarding its physic-chemical and biological properties, within in vitro and ex vivo studies, aiming to optimize the combination of Alg and nanoHA within the established system for maximizing the bone regeneration process.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The osteoconductive/osteoinductive, biocompatibility and bioactivity properties of nanoHA materials [7,28] combined with the injectability, biocompatibility and biodegradation properties of Alg polymers [29,30] can improve the physic-chemical and cell adhesion/tissue development of the attained composites, enhancing bone tissue regeneration [31][32][33]. However, these properties could be dependent on the amount of ceramic nanoparticles used within the polymer-based composite, as observed by other authors [21][22][23]. In this context, in the present study, the influence of nanoHA content on an alginate-based hydrogel system was studied, regarding its physic-chemical and biological properties, within in vitro and ex vivo studies, aiming to optimize the combination of Alg and nanoHA within the established system for maximizing the bone regeneration process.…”
Section: Discussionmentioning
confidence: 88%
“…Once nanoHA is gradually degraded, it releases calcium (Ca 2+ ) and phosphate (PO 4 −3 ) ions, which can modulate cellular behavior within the microenvironment, through different signaling pathways, influencing the bone mineralization process and bonding to the surrounding tissues [21]. Accordingly, some authors have reported that the level of solubility, bonelike apatite layer formation, cell attachment, proliferation and differentiation and, ultimately, bone growth rate, could be dependent on the concentration of nanoHA incorporated into polymer-based composites [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher weight loss was observed for PC‐20 having greater CLN content than PC‐0 (Table S2). This suggests that the plasticizing effect of CLN on PCEC chains might have resulted in further bulk degradation due to increased water resorption and thus movement of polymer chains (Salmasi, Nayyer, Seifalian, & Blunn, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cyclic peptides have low inherent toxicity, can be efficiently synthesized and easily labeled (25). Salmasi et al (53) reported that the number of seed cells, and cell adhesion and expansion on biomaterial scaffolds determined the ability of bone tissue regeneration in bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%